L’intérêt d’un fonds international de désarmement pour le développement (Note) - Fontanel, Jacques (Études internationales, 1985)
By passing the usual debate on the UNESCO "crisis", this paper analyses the ideological contradictions found in the Constitutive Act of the Organisation, and goes on to examine, using the model of small group psychology, the functioning of its main institutions, particularly that of the General Conference, by focusing on the disparity between its mandate and the role which it fulfils in effect. The purpose of the rites which preside over the debates at the General Conference and the Executive Council is questioned, specially as regards the origin and nature of the rhetoric which flourishes at those levels. Finally, the author examines the institutional, political and psychological constraints which have a negative influence on the effectiveness of the Secretariat and which also contribute to the drift of the Organisation.